Factors that Mitigate the Formation of Emerging Disinfection By-Products in Recycled Water - Linge, K.; Allard, S.; Liew, D.; Toulliou, C.; Heitz, A.; Joll, Cynthia; Edwards, B.; Charrois, J. (2012)
Previous research indicates that some disinfection by-products (DBPs) can form within water recycling plants utilising membrane treatment processes, specifically as a result of the chloramination pretreatment step protecting reverse osmosis (RO) membranes from excessive biofouling. Here we report the results from laboratory studies and field sampling that demonstrate that key factors influencing N-nitrosamine formation are precursor removal in the wastewater treatment plant (WWTP), and appropriate control of chloramination in RO treatment. A pilot plant study of the impact of pH and contact time on DBP formation further highlighted the importance of chloramine speciation on a range of DBPs. In particular, the formation of iodinated-THMs is reported, with speciation influenced by iodide concentration.